Effect of financial accounting standards implementation on the quality of MSME financial statements - Natalia, Ayunda (Yayasan Cinta Negara Indonesia, 2025)
The implementation of Financial Accounting Standards (FAS) plays a critical role in improving the quality of financial statements, particularly for Micro, Small, and Medium Enterprises (MSMEs). This study aims to examine the effect of FAS implementation on the quality of MSME financial statements in terms of relevance, reliability, comparability, and understandability. Using a quantitative research design, data were collected through structured questionnaires distributed to 120 MSME owners and accountants across various sectors. The responses were analyzed using multiple linear regression to assess the relationship between the level of FAS implementation and the perceived quality of financial reporting. The results indicate that the proper adoption of FAS has a significant positive impact on all dimensions of financial statement quality. MSMEs that fully comply with FAS tend to produce more accurate, transparent, and consistent reports, enhancing stakeholder trust and decision-making effectiveness. However, the study also reveals that a lack of technical knowledge, limited resources, and inadequate training remain major barriers to optimal FAS implementation. These findings highlight the need for targeted capacity-building programs, simplified reporting guidelines, and government support to ensure broader compliance among MSMEs. The research contributes to the literature by providing empirical evidence of the crucial role FAS plays in improving financial reporting quality and offers practical implications for policymakers, regulators, and business owners aiming to strengthen MSME financial governance